(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
To solve the problems of wheelchair users’ shoes and boots in the aspects of convenience, warmth, and comfort in low-temperature environments and better meet their physiological and psychological needs, this paper proposes a structural design scheme of easy-to-wear and take-off warm boots based on a new type of warm wadding. At the same time, the fuzzy mathematics comprehensive evaluation method was used to select a new kind of flocculant with excellent thermal and wet comfort polyester fiber flocculant as the filling material for the follow-up warm boots. This paper has guiding significance and application value to the development and application of wheelchair users to put on and take off warm boots.